Students' Perceptions on Corporate Social Responsibility at the Academic Level. Case Study: The Faculty of Administration and Business, University of Bucharest - Marin Burcea; Paul Marinescu (Amfiteatru Economic Journal, 2011)
During the last decades, the social responsibility of institutions, public as well as private, has been subject to intense debates, activities and academic research. The aims of the paper are to highlight in short the importance of the social responsibility of institutions, and to analyze the results of a research regarding students' perceptions on corporate social responsibility activities of a Romanian university. By using primary data obtained from a survey based on a questionnaire a set of three hypotheses was tested during our research. The information was processed by using the SPSS software. The results of our research emphasize that students attach importance to the corporate social responsibility at academic level, a fact indicated through their involvement degree in the specific activities of this concept.
Keywords: M14; 330; social responsibility; corporate social responsibility; students; university